2006
DOI: 10.1196/annals.1378.073
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the E2F Family of Transcription Factors and Its Clinical Relevance in Ovarian Cancer

Abstract: The E2F family of transcription factors plays a pivotal role in the regulation of cellular proliferation. On the basis of sequence homology and function, eight distinct members of E2F transcription factors (E2F-1 to E2F-8) have been distinguished to date. The regulation of E2F transcription factors is closely associated with the function of the retinoblastoma family of tumor suppressors (RB pathway). In the last decade various alterations of distinct components of the RB-E2F pathway were found to be associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
60
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 17 publications
7
60
0
Order By: Relevance
“…The latter include E2F, a positive regulator of transcription (13) and EP300, a histone acetyltransferase that releases promoter activity via chromatin remodeling (14). Another key element is the retinoblastoma protein (Rb), which, by forming a complex with the tyrosine kinase ABL (15), suppresses the transcriptional complex (16).…”
mentioning
confidence: 99%
“…The latter include E2F, a positive regulator of transcription (13) and EP300, a histone acetyltransferase that releases promoter activity via chromatin remodeling (14). Another key element is the retinoblastoma protein (Rb), which, by forming a complex with the tyrosine kinase ABL (15), suppresses the transcriptional complex (16).…”
mentioning
confidence: 99%
“…The expression levels of E2F1, E2F2, and E2F8 were elevated in the ovarian cancer cells (27). Besides, E2F1 was overexpressed in breast cancers (28), pancreatic ductal carcinoma (29), and gastric cancer (30).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that transcription factor E2F1 interacts with the p53 and PI3K pathway. (Hallstrom, Mori, & Nevins, 2008;Reimer et al, 2006; Its role in ovarian cancer has been unclear, as other research groups have found similar favourable survival with increased E2F1 pathway activation (Hallstrom et al, 2008), while other findings have shown favourable survival with decreased E2F1 gene expression by RT-PCR. (Reimer et al, 2006; It must be remarked that the latter study included an overrepresentation of patients with clear cell carcinomas (42.9%) and may be less informative here.…”
Section: Discussionmentioning
confidence: 83%